Effectiveness of online grammar websites on achievement and motivation of second language (L2) students in learning English grammar / Shukri Ismail - Ismail, Shukri (2009)
The purpose of this study was to investigate the effect of using online grammar websites on students' achievement and motivation in learning English grammar. A 2 x 2 quasi-experimental design was used in this study. The independent variables were the teaching methods - computer-based and conventional method. The dependent vaiables were the achievement score and motivational score. A sample consisting of 120 Form 2 students who were divided into two main groups, the good students and the weak students. The achievement scores and the motivational score were obtained through pre-test and post-test and Keller's Instructional Materials Motivation Scale (IMMS) respectively. The gain scores used to compared the achievement of students were obtained from the difference between the post-test scores and the pre-test scores. The result of the study were suppotive of the use of online grammar websites as it has a significant effect on both, the weak and good students. The implication of this study is that the appropriate use of online grammar websites has the potential to significantly improve the achievement and the motivation of students in learning English grammar. Besides this implication, the findings also could contribute towards improving the teaching and learning process of English language in Malaysian schools.